Pengaruh Kualitas Pelayanan dan Kepuasan Nasabah Terhadap Loyalitas Nasabah di Bank BRI Unit Vila Gading Permai Jakarta Utara - Mawarni, Resa; Sofyan, Mohammad (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This research is motivated by the phenomenon of insufficient achievement of customer loyalty targets at Bank BRI Vila Gading Permai Unit, North Jakarta. This is influenced by various factors, including service quality that does not fully meet the customer expectations and insufficient customer satisfaction with the services provided. This phenomenon is reflected from the data showing that the achievement of deposit targets and customer satisfaction has not reached the expected target, which indirectly affects the level of customer loyalty. This research uses a quantitative method, with data collected through a questionnaire that has been tested for validity and reliability. The population in this research consists of customers registered at Bank BRI Vila Gading Permai Unit, North Jakarta, totaling 20,562 customers, with a research sample of 100 respondents selected using the purposive sampling technique. The data analysis technique used is multiple linear regression analysis with SPSS for Windows Ver.27. The results of this research indicate that: (1) service quality has a positive and significant effect on customer loyalty with a significance value of 0.001 and a contribution of 77.7%; (2) customer satisfaction has a positive and significant effect on customer loyalty with a significance value of 0.002 and a contribution of 77.5%; (3) service quality and customer satisfaction simultaneously have a positive and significant effect on customer loyalty with an R2 value of 79.9 or 79.9%, while the remaining 20.1% is influenced by other factors outside this research.